Agricultural Biotechnology for Sustainable Agriculture and Rural Development - A., Shyamala (International Journal of Bio-resource and Stress Management, 2023)
Technology application that uses biological systems living organizing or their derivatives to make or modify products or processes for specific uses is known as Biotechnology. Agricultural biotechnology is a collection of scientific techniques, including genetic engineering that is used to modify and improve plants, animals and microorganisms for human benefit. The present shady explores the roles biotechnology may play in contributing to sustainable agriculture and rural development with particular concerns for bio safety and bio-diversity. Plant biotechnology research is applied to well define social or economic objectives, such as improving the food staples of the poor. An objective of biotechnology is now dependent on private investment not on the Government level. Long – term public sector investment in agricultural research is essential to address the needs of poorer farmers. Increased participation by farmers in sustainable agriculture and rural development process is of vital concern. Many actions in several fields need to be developed by Governments to make sure that the pro-poor potentialities of agricultural biotechnologies are realized.